SIKAP PESERTA DIDIK KELAS VIII TERHADAP ROKOK DI SMP NEGERI 23 PADANG - -, Gusrefnidarti - (Bimbingan dan Konseling, 2014)
This research was motivated by the phenomenon that the researchers found in the fieldwhere the students found smoking bandwagon, their students to his friend asking for money to buycigarettes, their learners like or dislike the smell of cigarette smoke, the students holding acigarette in the yard of the school, their learners feel associate with smoking. Study the researchersraised concerns about the attitude of students of class VIII of SMP Negeri 23 cigarettes in Padang.This type of research is descriptive quantitative method. The study population was a classVIII students SMP Negeri 23 Padang. The samples in this study using simple random samplingtechnique. From the results of the calculation obtained a sample of 70 people. The instrumentsused in the study was a questionnaire. Formula used to analyze the data in order to see thepercentage of students in class VIII attitudes to smoking in SMP Negeri 23 Padang.The results of the analysis of the data obtained: (1) The attitude of students towardssmoking in terms of response to cognitive evaluative criteria very well. (2) The attitude of studentstowards smoking in terms of affective evaluative response to the criteria quite well. (3) Theattitude of students towards smoking in terms of behavioral responses to the evaluative criteriavery well. So the results, on the attitude of students of class VIII to smoking in SMP Negeri 23Padang that the attitude is good enough so that learners do not smoke and stay away fromcigarettes.